Does culture influence what and how we think? Effects of priming individualism and collectivism - Oyserman, Daphna; Lee, Spike W S (Psychological bulletin, 2008)
Do differences in individualism and collectivism influence values, self-concept content, relational assumptions, and cognitive style? On the one hand, the cross-national literature provides an impressively consistent picture of the predicted systematic differences; on the other hand, the nature of the evidence is inconclusive. Cross-national evidence is insufficient to argue for a causal process, and comparative data cannot specify if effects are due to both individualism and collectivism, only individualism, only collectivism, or other factors (including other aspects of culture). To address these issues, the authors conducted a meta-analysis of the individualism and collectivism priming literature, with follow-up moderator analyses. Effect sizes were moderate for relationality and cognition, small for self-concept and values, robust across priming methods and dependent variables, and consistent in direction and size with cross-national effects. Results lend support to a situated model of culture in which cross-national differences are not static but dynamically consistent due to the chronic and moment-to-moment salience of individualism and collectivism. Examination of the unique effects of individualism and collectivism versus other cultural factors (e.g., honor, power) awaits the availability of research that primes these factors.